Florfenicol-Polyarginine Conjugates Exhibit Promising Antibacterial Activity Against Resistant Strains - Li, Zhun; Yang, Ya-Jun; Qin, Zhe; Li, Shi-Hong; Bai, Li-Xia; Li, Jian-Yong; Liu, Xi-Wang (Frontiers in Chemistry, 2022)
Florfenicol was widely used as antibiotic in the livestock and poultry breeding industry, resulting in a serious problem of drug resistance. In order to solve the resistance of florfenicol, this study designed and synthesized a new series of florfenicol-polyarginine conjugates and tested for antimicrobial activities. Drug-sensitive bacteria, gram-negative bacteria Escherichia coli (E. coli) and gram-positive Staphylococcus aureus (S. aureus), were sensitive to several of the compounds tested. These conjugates also showed excellent activity against drug-resistant strains such as methicillin-resistant S. aureus (MRSA) and florfenicol resistant Escherichia coli strains (2017XJ30, 2019XJ20), one of which as E6 had a minimum inhibitory concentration of 12.5 μmol/L. These conjugates did not allow bacteria to develop resistance and also decreased bacterial growth by membrane depolarization and disruption. Additionally, florfenicol succinate (C1) showed certain activity after coupling with arginine. This suggested that conjugating arginine to florfenicol succinate effectively modulated the properties of prodrugs. These new conjugates may provide useful insights for expanding the pool of antibiotics.